2008
DOI: 10.1088/1752-7155/2/3/037013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of breath, exhaled via the mouth and nose, and the air in the oral cavity

Abstract: Analyses have been performed, using on-line selected ion flow tube mass spectrometry (SIFT-MS), of the breath of three healthy volunteers, as exhaled via the mouth and the nose and also of the air in the oral cavity during breath hold, each morning over a period of one month. Nine trace compounds have been quantified and concentration distributions have been constructed. Of these compounds, the levels of acetone, methanol and isoprene are the same in the mouth-exhaled and the nose-exhaled breath; hence, we ded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
202
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 146 publications
(227 citation statements)
references
References 36 publications
19
202
6
Order By: Relevance
“…A study reported by Turner et al found high inter-individual variations in breath concentrations of acetone with mean values ranging from 148 to 2744 ppb (Caucasian volunteers) [40] . Wang et al, also reported similar intra and inter individual variations in breath acetone concentrations (a mean value of 636 ppb; three volunteers monitored over a period of 30 days) [41]. These variations in acetone concentrations are not unusual as breath acetone is entirely systemic in origin [42].…”
Section: Citationmentioning
confidence: 81%
See 1 more Smart Citation
“…A study reported by Turner et al found high inter-individual variations in breath concentrations of acetone with mean values ranging from 148 to 2744 ppb (Caucasian volunteers) [40] . Wang et al, also reported similar intra and inter individual variations in breath acetone concentrations (a mean value of 636 ppb; three volunteers monitored over a period of 30 days) [41]. These variations in acetone concentrations are not unusual as breath acetone is entirely systemic in origin [42].…”
Section: Citationmentioning
confidence: 81%
“…Concentrations for acetaldehyde (39.6-46.2 ppb) observed in the present study are also similar to the concentrations observed in the literature reports. Literature reports are mainly based on breath examination of Caucasian populations [41,47], which could explain the differences observed in the breath concentrations of certain VOCs.…”
Section: Citationmentioning
confidence: 99%
“…The sampling flow was reduced to the desired rate using a short length of 1/16 inch PTFE tubing which possessed an internal diameter of 0.007 inch [9]. The compounds of interest (sulphides, organic acids, ammonia, isoprene and acetone) were quantified by monitoring the specific ion product of the reaction between the compound of interest and the precursor ion transformed into absolute concentrations using a predetermined reaction rate coefficient [6][7][11][12][13][14] . Precursor ion count rates for all ions exceeded 800 000 cps, with precursor ion purity exceeding 98.5%.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, bacteria present in the mouth, in particular the dorsal surface of the tongue, catabolise food stuffs to produce a variety of chemicals, some of which result in little odour at typical concentrations, such as ammonia [6], while others are a source of malodour [5]. The predominant odiferous compounds derive from sulphur-containing amino acids and include hydrogen sulphide (H 2 S), methylmercaptan (CH 3 SH), dimethylsulphide (CH 3 SCH 3 ), and dimethyldisulphide (CH 3 S 2 CH 3 ), although additional compounds such as short-chain organic acids (butyric, propionic and valeric), polyamines and indole may also contribute [5].…”
mentioning
confidence: 99%
“…Conversely, cyanide is absent from the sputum of bronchiectasis patients without P. aeruginosa infection [5,6] and HCN is very low or absent from the breath of healthy children [8]. Studies in healthy adults have shown that much of the HCN is generated in the mouth and this could have importance when measuring HCN in exhaled breath in relation to infection with P. aeruginosa [9].…”
mentioning
confidence: 99%